1997
DOI: 10.1095/biolreprod56.5.1198
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Sperm Binding to Oviductal Epithelium Involves Fucose Recognition1

Abstract: Sperm binding to oviductal epithelium probably serves to form the isthmic sperm reservoir. This interaction of sperm and oviductal epithelium may involve species-specific carbohydrate recognition. We tested a series of carbohydrates and glycoproteins for inhibition of bovine sperm binding to oviductal epithelium in vitro. Explants of isthmic and ampullar epithelium were obtained from oviducts that had been surgically removed from preovulatory heifers. The explants were incubated (39 degrees C, 5% CO2) with fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
104
0
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(113 citation statements)
references
References 51 publications
(64 reference statements)
4
104
0
5
Order By: Relevance
“…While the number of canine spermatozoa that bound to canine and porcine oviducts was similar [48], the number of ejaculated boar spermatozoa in our study that bound to the isthmus (but not ampulla) was significantly less in cows than gilts. This result suggests that binding is preferentially species-specific because carbohydrate-binding lectins and glycoconjugates present on the plasma membrane of the sperm head and surface of oviductal epithelium may vary considerably among species [29,50]. Thus we concluded that it was necessary to use porcine oviducts for remaining experiments despite the increased cost and logistical difficulties associated with such an experimental set-up.…”
Section: Discussionmentioning
confidence: 92%
“…While the number of canine spermatozoa that bound to canine and porcine oviducts was similar [48], the number of ejaculated boar spermatozoa in our study that bound to the isthmus (but not ampulla) was significantly less in cows than gilts. This result suggests that binding is preferentially species-specific because carbohydrate-binding lectins and glycoconjugates present on the plasma membrane of the sperm head and surface of oviductal epithelium may vary considerably among species [29,50]. Thus we concluded that it was necessary to use porcine oviducts for remaining experiments despite the increased cost and logistical difficulties associated with such an experimental set-up.…”
Section: Discussionmentioning
confidence: 92%
“…In cows, for example, fucose mediates the tight attachment of sperm to the oviductal epthelium (Lefebvre et al 1997), inhibiting sperm movement, whereas D. melanogaster sperm maintain some motility while in storage (Lefevre and Jonsson 1962). We instead propose three potential mechanisms that might explain Acp29AB's role in sperm storage:…”
Section: Discussionmentioning
confidence: 99%
“…In a number of mammals, sperm are stored for several hours in an oviductal reservoir, in which sperm are bound tightly to the epithelium of the oviduct (e.g., Suarez and Osman 1987). Carbohydrates mediate the adherence of sperm to the epithelium, with different sugars playing important roles in different species (e.g., Demott et al 1995;Lefebvre et al 1995Lefebvre et al , 1997Ekhlasi-Hundrieser et al 2005). In cows, for example, biochemical studies suggest that fucose residues on oviductal annexins act as receptors for sperm, with several sperm-bound seminal proteins recognizing the fucose moiety (Ignotz et al 2001(Ignotz et al , 2007Gwathmey et al 2006).…”
mentioning
confidence: 99%
“…Although a considerable amount of knowledge has been gained especially in human and mouse (Almeida et al 1995, Bronson & Fusi 1996, Fusi et al 1996a, 1996b, Nixon et al 2007, Vjugina & Evans 2008, the exact mechanisms of the molecules involved in bovine fertilization are not unequivocally identified at present. Carbohydrates and glycoproteins are assumed to modulate adhesion and binding events during consecutive reproductive processes, like sperm-oviduct adhesion (Lefebvre et al 1997, Suarez et al 1998, Revah et al 2000, Talevi & Gualtieri 2001, Sostaric et al 2005, Ignotz et al 2007, sperm-oocyte interactions (Tulsiani et al 1997, Gougoulidis et al 1999, Amari et al 2001, Tanghe et al 2004a, 2004b, and embryo implantation (Whyte & Allen 1985, Biermann et al 1997.…”
Section: Introductionmentioning
confidence: 99%